2022
DOI: 10.1002/gcc.23088
|View full text |Cite
|
Sign up to set email alerts
|

3′RNA and whole‐genome sequencing of archival uterine leiomyomas reveal a tumor subtype with chromosomal rearrangements affecting either HMGA2, HMGA1, or PLAG1

Abstract: Uterine leiomyomas, or fibroids, are very common smooth muscle tumors that arise from the myometrium. They can be divided into distinct molecular subtypes. We have previously shown that 3′RNA‐sequencing is highly effective in classifying archival formalin‐fixed paraffin‐embedded (FFPE) leiomyomas according to the underlying mutation. In this study, we performed 3′RNA‐sequencing with 111 FFPE leiomyomas previously classified as negative for driver alterations in mediator complex subunit 12 (MED12), high mobilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…From these tumors, 38% in one study showed overexpression of HMGA1 [ 28 ]. Another study focused on 111 tumors, which were classified as negative for driver alteration based on Sanger sequencing and immunohistochemistry [ 17 ]. Forty-three of these tumors (39%) showed features typical for HMGA2-altered tumors including PLAG1 overexpression and 16 of them (14%) chromosomal rearrangements of HMGA2 (despite not having overexpression of HMGA2 by IHC), HMGA1 , or PLAG1 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…From these tumors, 38% in one study showed overexpression of HMGA1 [ 28 ]. Another study focused on 111 tumors, which were classified as negative for driver alteration based on Sanger sequencing and immunohistochemistry [ 17 ]. Forty-three of these tumors (39%) showed features typical for HMGA2-altered tumors including PLAG1 overexpression and 16 of them (14%) chromosomal rearrangements of HMGA2 (despite not having overexpression of HMGA2 by IHC), HMGA1 , or PLAG1 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, they have been suggested to be a secondary event related to tumor progression. Nevertheless, aberrations of both genes can occur also as an isolated finding and can be a driver event in uterine leiomyoma [ 17 ]. Other rare molecular driver aberrations occurring in uterine leiomyoma included somatic mutations in genes encoding six members of SRCAP histone-loading complex leading to H2A.Z loading defect [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations